The effect of acute high-intensity interval training and Tabata training on inhibitory control and cortical activation in young adults - Shao, Xueyun; He, Longfei; Liu, Yangyang; Fu, Yang (Frontiers in Neuroscience, 2023)
Physical exercise not only benefits peoples’ health, but also improves their cognitive function. Although growing evidence suggests that high intensity interval training (HIIT) is a time-efficient exercise regime that can improve inhibitory control performance by enhancing cortical activation in the prefrontal cortex, less is known about how Tabata training, a subset of HIIT that requires no equipment or facilities to perform, affects inhibitory control and cortical activation in young adults. Therefore, we aimed to reveal the effect of an acute bout of HIIT and Tabata training on inhibitory control and attempted to identify its potential neural substrates. Forty-two young adults (mean age: 19.36 ± 1.36 years; 21 females) performed the Stroop task and Simon task before and after acute HIIT, Tabata training, or a control session, and cortical hemodynamic changes in the prefrontal area were monitored by functional near-infrared spectroscopy (fNIRS) during the tasks. Both HIIT and Tabata interventions lasted for a total of 12 min. The HIIT participants performed ergometer cycling at their 80% maximal aerobic power at 90 to 100 rpm, and the Tabata participants performed a total of 8 intense activities, such as jumping jacks, high knees and butt kickers, without using equipment or facilities, keeping the heart rate at 80% to 95% of their maximum heart rate. Participants in the control group watched a sport video while sedentary. Cognitive tasks data and fNIRS data were analyzed by repeated-measures three-way ANOVA. Our results indicated that both the HIIT and Tabata groups exhibited reduced reaction times after the intervention, and there were alterations in activation patterns in the dorsolateral and ventrolateral prefrontal cortices.